Projektowanie scenariuszy promocji cenowych z wykorzystaniem wielorównaniowych ekonometrycznych modeli popytu konsumpcyjnego - Błażejowski, Marcin; Kufel, Tadeusz (Designing Price Promotion Scenarios with Use of Econometric Multiequation Models of Consumer Demand, 2007)
The paper concern problems of construction of dynamic simultaneous multiequation models of consumer demand, estimated on the basis of daily sales time series derived from supermarket. The example concern market of washing powders. Presented results of dynamic simulations for four brands of washing powders, based on different promotion scenarios (different combinations of promoted brands in the same time and shifting of start point of the promotions) proofs, that customer's reactions on price promotions are different and depend on scale of promotion and promoted brand.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Taksonomia (14); 2007; nr 1169, s. 515-522